Global Challenges and Population’s health; Report on the International Conference on 19-20 November 2021 - Ataniyazova, Oral; Moshammer, Hanns; Yari, Saeed; Mosavi, Alireza (Asian Pacific Journal of Environment and Cancer, 2021)
-